Implementation of Moral Dilemma Discussion as an Effort to Strengthen Student Character through Internalization of Tolerance Values - Putri, Astri Komara; Ganeswara, Ganjar Muhammad; Warlim, Warlim (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2023)
Indonesian society is known as a nation with pluralism of religious, ethnic, cultural, and ethnic diversity. Various kinds of problems that commonly occur related to the lack of tolerance are still a concern to many parties. This is considered a threat to the nation, especially in terms of diversity in Indonesia. Many social conflicts have occurred due to the issue of inter-faith tolerance in society. In line with education, the Indonesian current curriculum, named Kurikulum Merdeka, has also been present and designed the profile of Pancasila students to develop a stronger character against the challenges of the 21st century. Global diversity is one of the dimensions for presenting respectful and tolerant life in a nation. In this research, there is a discussion about the role of higher education students in anticipating problems related to tolerance values. Therefore, the researcher made observations by collecting some data regarding on how the internalization of tolerance values was integrated into learning activities through moral dilemma discussion as an effort to strengthen the character of students at Siliwangi University, Tasikmalaya. An internalization method is a cognitive approach based on Lawrance Kohlberg's theory, considered capable of realizing one's moral reasoning so that it will become the basis of good moral judgment. Therefore, the researcher provides a description of the planning, implementation, and results of internalizing the value of tolerance through moral dilemma discussion.